Consumption of alcohol-based hand rub in French nursing homes: results from a nationwide survey, 2018–2019. (December 2021) - Ali-Brandmeyer, O.; Blanckaert, K.; Nion-Huang, M.; Simon, L.; Birgand, G.; ,
Summary: This study assessed the hand hygiene performance in French nursing homes using the consumption of alcohol-based hand rubs (AHRs) as a surrogate. Nursing homes from the 17 French regions were contacted to collect their AHR consumption and occupancy in 2018 and 2019. A total of 1290 nursing homes from 15 French regions participated in the survey. The estimated median number of hand hygiene actions per resident-day was 1.48 (interquartile range: 1.04–2.03) in 2018 and 1.60 (1.10–2.26) in 2019. A significantly higher AHR consumption was observed in public nursing homes with an infection control team or link nurse.